Strategi Guru Dalam Menangani Siswa Yang Kesulitan Belajar di SMP Az-Zakiyyah Islamic School - Gita Asyari; Rasyita Dewi Lubis; Shahnaz Alissa Siregar; Abdul Fattah Nasution (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
Learning difficulties experienced by students remain a major challenge in education, including at SMP Az Zakiyyah Islamic School. This study aims to analyze teachers’ strategies in addressing students with learning difficulties. A descriptive qualitative approach was employed, using observation, interviews, and documentation involving teachers, students, and school staff. The results revealed that students faced various types of difficulties, including cognitive, motivational, socio-emotional, and language-related issues. Teachers implemented early identification, remedial programs, spiritual reinforcement, and collaboration with counselors and parents. These strategies proved effective in improving academic performance, learning motivation, and students' spiritual and social behavior. The findings highlight the critical role of teachers in designing adaptive strategies rooted in Islamic values to support inclusive learning.